Media education in basic education. A project in the library context. - Simões de Almeida, M.; Matos, A. P. M.; Bobrowicz-Campos, E.; Lourenço, A. (ICCL 2021 Proceedings – Livro de Atas e Livro de Resumos, 2021)
In Portugal, the media education is implemented in the school context, in the discipline of Citizenship and Development, according to the referential National Strategy for Citizenship Education (Directorate−General for Education, 2017), and in collaboration with the schools libraries. A recent study on media literacy in the context of schools libraries in Portugal (Pereira & Toscano, 2021) revealed the existence of some difficulties in developing activities in this area, related to the lack of availability and training of teachers and schools in general, and the lack of means and resources. Based on the difficulties showed in the literature, a media education project was designed with students of basic education in the context of an internship of the second year of the Master in Social Education, Development and Local Dynamics, being developed in the library of School Cluster Martim de Freitas, in Coimbra, Portugal. This project aims to promote critical reflection in students on different themes that are very present in their lives and in their relationship with the media (such as video games, advertising and cyberbullying), as well as create resources that become available for future use by the library team and teachers in general. These activities take place in person, in the library space, and also online, with the latter being designed for the non−classroom teaching period resulting from the covid−19 pandemic. In this work, it is intended to present the project development and promote reflection on the importance of school libraries for the improvement of students’ media literacy.